Neurofluid circulation changes during a focused attention style of mindfulness meditation - Bryce A. Keating; David Vago; Kilian Hett; Ciaran Considine; Maria Garza; Caleb Han; Colin McKnight; Daniel O. Claassen; Manus J. Donahue (Proceedings of the National Academy of Sciences, 2025)
Neurofluids, including cerebrospinal fluid (CSF) and interstitial fluid, circulate through regulated central nervous system pathways to clear cerebral waste and support brain health, with elevated CSF flow hyperdynamicity and regurgitation through the cerebral aqueduct associating with aging and neurodegeneration. Sleep exerts state-dependent effects on neurofluid circulation, yet similar modulation during unique waking states, such as meditation, remains underexplored. Notably, mindfulness meditation shares several regulatory features with sleep, with core meditation practices representing distinct arousal states. We investigated whether the focused attention (FA) style of mindfulness meditation modulates neurofluid dynamics directionally opposite to aging and consistent with sleep. Using phase-contrast MRI, we assessed absolute CSF flow and velocity through the aqueduct, and using blood oxygenation level–dependent (BOLD) MRI, we assessed CSF fluctuations near the cervicomedullary junction together with total supratentorial gray matter fluctuations. Assessments were repeated in meditation-naïve adults during mind wandering (MW) without (n = 13; repeatability controls) and with (n = 14; breath controls) respiration rate modulation and in adept meditators (n = 23) during MW and FA meditation. No aqueduct CSF flow changes were observed in control groups. In meditators, aqueduct absolute CSF flow motion decreased from MW to FA meditation (4.60 ± 2.27 mL/min to 4.17 ± 2.10 mL/min, P = 0.005) owing to reduced regurgitant cranially directed CSF flow velocity. On BOLD, this paralleled increased low-frequency (0.0614 to 0.0887 Hz) CSF fluctuations ( P = 0.0138), which were inversely correlated with gray matter fluctuations during FA meditation. Findings suggest that mindfulness meditation may represent a nonpharmacological, waking state capable of modulating neurofluid dynamics in a directionally similar manner to sleep and opposite to aging and neurodegeneration.